A study to establish the most plausible background to the Fourth Gospel (John) - Magezi, Vhumani (HTS teologiese studies, 2010)
The quest to establish a conceptual background of the fourth gospel has led to converging and diverging opinions. This study reviewed and compared literature on the fourth gospel to establish its most plausible background. In doing so, attention was given to the development of the debate on the religious backgrounds that possibly influenced the author in order to discover some fresh connections between the gospel and these suggested backgrounds. Reference is made to primary material such as the Dead Sea Scrolls, first century Palestinian Judaism, Josephus and Philo of Alexandria. The following proposed backgrounds were reviewed: Hellenistic Judaism, Philo of Alexandria, Gnosticism, Hermetic Literature, Mandaism, the Old Testament, Rabbinic Judaism, the Dead Sea Scrolls and the Samaritan background.